Risk level for type 2 diabetes in people attending outpatient clinics in a public hospital in Morelia, Michoacán, México - Ruiz-Recéndiz, Ma. de Jesús (2022)
Objective: To evaluate the level of risk for type 2 diabetes in persons attending outpatients at a public hospital in Morelia, Michoacán, Mexico. Method: Quantitative study with descriptive and cross-sectional design; a probability sample of 327 persons selected by simple random sampling, users of a public hospital. FINDRISC instrument that measures risk for type 2 diabetes. Descriptive statistics were used for the analysis in the SPSS v.25 program. The right of withdrawal and confidentiality were respected. Main results: 100% of the participants were women; the majority were adults (75.5%), married (25.7%), housewives (59.9%), living in Michoacán (89%) and residents of Morelia (73.4%). It was also found that 36.4% of the subjects were overweight, 59.6% with abnormal blood pressure and 56% with normal glucose. Very high risk of developing diabetes was found in 24.5% and high risk in 20.5%. There was a statistically significant relationship between risk for diabetes with age, schooling, marital status, and occupation (p>.05). General conclusion: Four out of 10 participants presented a very high and high level of risk of developing diabetes in the next 10 years, so nursing should develop a care plan according to the needs of the person at risk of developing the disease that allows establishing an axis of prevention or improvement.